Description of oral-motor development from birth to six years of age (2014)
This document seeks to present bibliometric research into characterizing the behaviors of each of the stomatognathic functions of a child based on developmental age and expected development until the age of six. The investigation collected the information provided in scientific literature regarding the development of oral-motor postural patterns, environmental influences, sensitivity, tone, muscle strength, use of feeding tools, anatomy, physiology, and the neurology of the anatomical structures of the stomatognathic system. As a result, the major milestones of oromotor development from birth to the age of six are described in this document. Also, a more detailed manual was written to be used by Speech-Language Pathologists. The research concludes that oral motor patterns emerge according to the maturation and function of the different stomatognathic structures. It is of prime importance for Speech-Language Pathologists to be experts in normal oromotor development in order to provide the best professional services when treating children in need of feeding, sucking and dysphagia therapy.